2008
DOI: 10.1007/s00134-008-1100-1
|View full text |Cite
|
Sign up to set email alerts
|

Internally coated endotracheal tubes with silver sulfadiazine in polyurethane to prevent bacterial colonization: a clinical trial

Abstract: SSD-ETT can be safely used in preventing bacterial colonization and narrowing of the ETT in patients intubated for up to 24 h (mean intubation time 16 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 33 publications
0
50
0
2
Order By: Relevance
“…This could explain the difference of thickness between the measurements in our study (500 or 2.5 m) and between the thickness described in precedent studies. 17,30,31,33 Indeed, we demonstrate that a part of biofilm still covers ETT despite rinsing.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This could explain the difference of thickness between the measurements in our study (500 or 2.5 m) and between the thickness described in precedent studies. 17,30,31,33 Indeed, we demonstrate that a part of biofilm still covers ETT despite rinsing.…”
Section: Discussionmentioning
confidence: 61%
“…11 Berra and co-workers 15,30 studied ETT biofilm from animals ventilated for 24 h, and found 750 m of thickness using electron microscopy and 65 m with confocal microscopy. In a clinical trial using confocal microscopy, the same authors demonstrated an accumulation of biological material within the ETT, ranging from 0 to 700 m. 31 We Except for subject 21, the same microorganisms were found in both sites. observed a global covering of the internal side of the ETT with optical microscopy and AFM.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…4 Several new ETT technologies have tested the incorporation of antibiotics into biomaterials, showing a possible decrease in lung colonization by pathogenic bacteria. [42][43][44][45][46][47] Although long-term use of antimicrobialimpregnated central venous catheters has shown no selection of bacterial resistance, 48 biofi lm formation has been associated with antibiotic-resistant pathogens and lack of antimicrobial penetrability into the biofi lm of the ETT. 41,49,50 Recently, an in vitro model evaluated the role of antimicrobial photodynamic therapy in the reduction of ETT biofi lm.…”
Section: Cuff Pressurementioning
confidence: 99%
“…45 Most recently, a large, randomized, multicenter study demonstrated a decrease in microbiologically proven VAP incidence in patients intubated with the silver-coated ETT, when compared with a standard ETT. 24 The study performed at 54 centers in the United States in 1,509 patients who required MV for more than 24 h showed a lower rate of microbiologically confi rmed VAP of 4.8% (37 of 766 patients) in the group randomized to the silver-coated ETT compared with 7.5% (56 of 743 patients) in the group randomized to an uncoated ETT ( P 5 .03, number needed to treat 5 37).…”
Section: Acknowledgmentsmentioning
confidence: 99%